Review On An Approach To Infer User Search Goals (International Journal of Engineering and Computer Science, 2014)
There have been recent interests in studying the goal behind a user's Web query so that this goalcan be used to improve the quality of a search engine's results. The inference and analysis of user searchgoals can be very useful in improving search engine relevance and user experience. In this paper, main focusis on the survey of infer user search goal approaches in previous study. Additionally this paper projected aframework to search various user search areas for a query by clustering the feedback sessions. Feedbacksessions are constructed from user click-through logs and can efficiently reflect the information needs ofusers. Additionally, a novel technique is projected to generate pseudo-documents to better represent thefeedback sessions for clustering.